2021
DOI: 10.3390/nu13030901
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Stress and Food Intake: Protective and Risk Factors for Stress-Related Palatable Food Intake in U.S. Adults

Abstract: (1) Background: The coronavirus (COVID-19) pandemic has caused disruptions to what people eat, but the pandemic’s impact on diet varies between individuals. The goal of our study was to test whether pandemic-related stress was associated with food intake, and whether relationships between stress and intake were modified by appetitive and cognitive traits. (2) Methods: We cross-sectionally surveyed 428 adults to examine current intake frequency of various food types (sweets/desserts, savory snacks, fast food, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 72 publications
2
31
0
7
Order By: Relevance
“…Similar relationships are also indicated by other authors, including an increase in consumption of animal products and snacks [ 53 , 113 ], increasing salty snacks [ 32 ], increasing fat consumption [ 31 ], increasing ‘junk food’ consumption [ 61 ], snacking between meals [ 59 ], increased use of alcohol [ 65 ], and increasing sweets [ 34 , 65 ], especially during the lockdown. Authors [ 35 , 69 , 114 ] indicated that the stress associated with pandemic influenced on increases in emotional food of consumption, tasty but with high energy value. It should be emphasized that poor food choices in the long term could result in increased risk factors for cardiovascular diseases, diabetes, and cancer [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar relationships are also indicated by other authors, including an increase in consumption of animal products and snacks [ 53 , 113 ], increasing salty snacks [ 32 ], increasing fat consumption [ 31 ], increasing ‘junk food’ consumption [ 61 ], snacking between meals [ 59 ], increased use of alcohol [ 65 ], and increasing sweets [ 34 , 65 ], especially during the lockdown. Authors [ 35 , 69 , 114 ] indicated that the stress associated with pandemic influenced on increases in emotional food of consumption, tasty but with high energy value. It should be emphasized that poor food choices in the long term could result in increased risk factors for cardiovascular diseases, diabetes, and cancer [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transition period associated with a pandemic situation, therefore, has the potential to change eating habits, forcing most people to stay at home, sometimes in home-offices, for long periods, often with unlimited access to food in home and less physical activity [ 28 ]. Staying at home for a long time may favor snacking between meals, eating ‘junk food’ snacks, and drinking alcohol, and it may affect the consumer’s individual choices about cooking at home, buying ready-to-eat products, as well as using takeaway food services [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The perceived risk of COVID-19 and guidelines for minimizing personal contact might have been discouraging consumers from using gastronomy during the pandemic [ 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratings (range = 1-5) were averaged over the 16 items into a mean score. Mean stress scores have been linked to child [23] and adult [24] intake, as well as altered feeding behaviors in parents and heightened appetite in adults [23,25]. Stress tertiles were created by splitting the ordered distribution into thirds, resulting in groups reporting low (range = 1-2.21), moderate (range = 2.25-3.09), and high (range = 3.13-5) stress levels.…”
Section: Covid-related Stressmentioning
confidence: 99%
“…Individuals tend to consume more palatable and less healthy foods during stressful life periods [62]. A greater decline in mental health or increased stress, boredom or anxiety from COVID-19 has been associated with increased ultra-processed, HFSS foods intake, decreased FV intake and using snacking as a coping mechanism [9,14,32,55,56,[63][64][65]. The increased HFSS snacking at the start of the pandemic may reflect such maladaptive coping mechanisms [63,66].…”
Section: In Context Of Covid-19 Researchmentioning
confidence: 99%